EDP Serviço Universal rebranding communication plan - Almeida, Rita Figueiredo de Carvalheira (2021)
The objective of this project is to develop a communication plan for the rebranding of EDP Serviço Universal. EDP Serviço Universal is the regulated market company. At the end of 2017, the Energy Services Regulatory Authority (ERSE) imposed on the EDP group to make a total separation of designation and image between the companies in the group providing regulated services - that is, they have a specific function in the electricity sector and are remunerated for this through electricity tariffs - and those operating in the liberalized market, such as EDP Comercial. At the beginning of 2020, EDP Serviço Universal had to make the brand change. Being a regulated market company, there are several restrictions on how it can communicate with their customers, being this one of the main obstacles. The communication of the name distinction between the other companies of the EDP group is another factor that had to be taken into account. The communication strategy integrates mostly traditional tools. It is a customized strategy dedicated to each customer segment. Before the implementation and definition of objectives, all external and internal factors were analyzed, using several members of the project team to align the information with the company's expectations. The project was developed and implemented. During twelve months and after several meetings with the Board of Directors of the current SU ELETRICADE, it was possible to implement this communication plan. After completing the rebranding project, the company decided to create a customer experience area where the author is currently responsible for the entire communication strategy.